Measuring epistemological beliefs in history education: An exploration of naïve and nuanced beliefs. (2017) - Stoel, Gerhard; Logtenberg, Albert; Wansink, Bjorn; Huijgen, Tim; van Boxtel, Carla; van Drie, Jannet
Highlights: Ideas about historical knowledge and knowing differ between educational levels. Beliefs about the subjective nature of history cannot be reliably operationalized. Scores on historical methodology correlate positively with interest and grade. On average Dutch history exam students might be labeled 'procedural objectivists'. More emphasis needed in history education on explicit epistemological reflection. Abstract: This study investigates a questionnaire that measures epistemological beliefs in history. Participants were 922 exam students. A basic division between naïve and nuanced ideas underpins the questionnaire. However, results show this division oversimplifies the underlying structure. Exploratory factor analysis extracted 5 factors, separating items connected to nature of knowledge from nature of knowing. Furthermore, EFA problematized the distinction between naïve and nuanced ideas on subjectivity. Experts also reported large variance on subjectivity; therefore, these items were excluded from the questionnaire. The final questionnaire contained 3 factors focusing on the objective nature of (1) historical knowledge and (2) historical knowing, and on (3) methodological criteria. Finally, differences between school tracks and relationships between epistemological beliefs, interest and history grade were explored.